ESTOQUE DE CARBONO DAS UNIDADES DE CONSERVAÇÃO DA MAIOR ÁREA ÚMIDA DO PLANETA – PANTANAL - PINHEIRO, João Marcello Medeiros; RIVABEN, Rodrigo Cyrino; PONTARA, Vanessa; BUENO, Marcelo Leandro (ANAIS DO ENIC, 2025)
-